Origin of the variability of the mechanical properties of silk fibers: 4. Order/crystallinity along silkworm and spider fibers. (17th September 2014) - Wojcieszak, Marine; Percot, Aline; Noinville, Sylvie; Gouadec, Gwénaël; Mauchamp, Bernard; Colomban, Philippe
<x xml:space="preserve">Abstract</x> The poor crystallinity of proteic fibers has fuelled an ongoing debate over their exact organization. We present a full‐range Raman comparison of Nephila madagascariensis spider and Bombyx mori silkworm silks that sheds some new light on that matter. On the one hand, a large variability is observed along the fibers in the −200 to 200 cm−1 spectral window, which is sensitive to the long‐range order signature of polyamide chains. This questions the validity of previous literature data considering silk fiber as a homogeneous material. On the other hand, the 'amide I' band is almost independent of the targeted point, which sets a limit to this widely used structure probe. In‐line mapping of the fibers showed that the extension of the ordered zones ranges between 1 and 3 µm. The correlation between the macromechanical behavior (the stress–strain curves) and the nanomechanics (Raman low wavenumber signatures) under controlled tensile strain demonstrates a Prevorsek's type microstructure: the macromolecular chains belong to both ordered and amorphous 'regions'. Copyright © 2014 John Wiley & Sons, Ltd.